First person - Paco López-Cuevas (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Paco López-Cuevas is first author on 'Transformed notochordal cells trigger chronic wounds in zebrafish, destabilizing the vertebral column and bone homeostasis', published in DMM. Paco is a PhD student in the lab of Paul Martin at the University of Bristol, Bristol, UK, investigating the role of inflammation in cancer progression.